Exploring The Impact of Digital-Political Literacy and Religious Observance on the Boycott Behaviour for Israeli-Associated Products - Dian Wahyu Novitasari (Spektrum, 2026)
In recent years, the discourse about the Israel - Palestine conflict has adorned the various taglines on social media. It may elicit various responses and opinions across the global community. This study aims to explore how digital literacy (X1), political literacy(X2), and religious observance (Y) jointly shape boycott behaviour (Z) toward Israeli-associated products within a multidimensional literacy framework. It applies a multivariate quantitative analysis using SEM-PLS model covering the participation from 240 respondents in East Java, Indonesia. The findings of this study confirm that both digital literacy and political literacy exert positive and significant direct effects on boycott behaviour, while religious observance demonstrates a significant negative direct effect on boycott behaviour. However, interestingly, this research also found that religious observance plays a crucial indirect role by significantly mediating the relationships between digital literacy and boycott behaviour, as well as between political literacy and boycott behaviour. Our further analysis reveals that religiosity functions less as a direct behavioural driver and more as a moral interpretive mechanism that channels informational and political awareness into ethically framed consumer actions. The novelty of this research contributes to enriching the literature of consumer activism and sustainable civic engagement.